Pengaruh Pelatihan Kerja dan Pengembangan Karir Terhadap Kinerja Karyawan Pada PT. Alita Praya Mitra Palembang - Nabilah, Adinda Valencia; Roswaty; Ulum, Muhammad Bahrul (Jurnal EMT KITA, 2023)
This research is a type of quantitative descriptive research with the aim of knowing the effect of job training and career development on employee performance at PT Alita praya Mitra Palembang. Data analysis techniques used in this study are validity test analysis, descriptive analysis, reliability analysis and multiple linear regression analysis. Data collection instrument using a questionnaire. Based on this study it can be concluded that Job Training (X1) has a positive effect on employee performance. This shows that ρvalue = 0.000 and <standard value which is 0.05 while t-count = 3.210 where this number is > 2.021 and career development (X2) has a positive effect on employee performance. This shows the results of ρvalue = 0.003 and <standard value 0 .05 while t-count = 4.057 where this number is > 2.021.